A argumentação "pró-vida" e pró-escolha" nas audiências públicas no Supremo Tribunal Federal: a relação entre doxa e endoxa - Egina Glauce Santos Pereira (2018)
The present time enables, in terms of theory and analysis, a broad production on rhetoric, once we coexist with growing pluralist issues as well as a higher demand for more elaborated argumentative constructions to support standpoints. Among Legal Studies it is not thatdifferent, especially because of the methodological changes which involve applying and understanding the norm, which cooperates to build a broader argumentative environment, becoming necessary to insert value as an element of application, besides the fact and the norm. This research aims, in the given context, to study the role of doxa in the argumentative construction of the pronouncements presented in Public Hearings (PH) of the constitutional actions ADI (Direct Action of Unconstitutionality) nº 3.510 and ADPF (Claim of Breachof Fundamental Precept (ADPF) nº54 , concerning the Brazilian Supreme Court (STF).Along the thesis, we intend to focus, first, on the role of doxa concerning the legislation which is produced on the pronouncements of the individuals involved in the PH, built by authority discourses which are based in a doxa related to the STF itself. A second role would be to allow an interconnection among legal, political and social discourses. It can be considered as an opinion, advisory and probative body, which allows the competent authority to open space so that the maximum number of people, who may suffer the consequences of such a decision, have an opportunity to manifest themselves before the outcome of the process. In the discursive production in the AP, in the STF, it uses endoxas (medical discourse, biomedical, biological, religious, as well as juridical, that was once unique) to reach society (representative of doxa). We find a clash between pro-life and pro-choice arguments, seeking legitimacy, through doxical elements, aimed at reaching society in general through a wide dissemination of the utterances by the media, both in real time by TV Justice, and by the permanence on the Internet, on Youtube, of the debates that took place in the AP. This explains why the decisions made by the STF need to be based and legitimated by society. For those decisions to be legitimate, they have to include the participation or the understanding of society, democracy requirement. Legitimacy is defined as the duty of the PH when it comes to constitutional control in the norms that regulate this procedure. To analyze how this legitimacy is build, we observe which are the elements of doxa involved in the creation of the arguments in PH and how they interfere in the creation of the discursive places and directly in the genre Ph in the STF.